The reliability and validity of the Turkish version of the Fibromyalgia Participation Questionnaire - Altan, Lale; Celiker, Reyhan; Ercan, Ilker; Birtane, Murat; Akgun, Kenan; Zateri, Coskun; Tastekin, Nurettin; Rezvani, Aylin; Aktas, Ilknur; Ozdolap, Senay; Dursun, Erbil; Dursun, Nigar; et al. (AVES, 2018)
Objective: The objective of this study was to test the reliability and validity of the Turkish version of the Fibromyalgia Participation Questionnaire (FPQ). Methods: One hundred and eighty-four female patients with fibromyalgia syndrome were included in the study. All patients filled out the Turkish FPQ (FPQ-T) questionnaire, which was obtained by translation from German according to the guideline for the process of cross-cultural adaptation The patients filled out the revised Fibromyalgia Impact Questionnaire (FIQ) and reevaluated the FPQ-T two hours later. Internal consistency reliability of the FPQ-T was assessed by calculating the ``if item deleted{''} using Cronbach's alpha and the ``item-total correction{''} coefficient for each item of the questionnaire. The consistency of the subscales and the correlation of the test-retest values were assessed. The test-retest values were compared using the Wilcoxon test. Criterion validity was measured using FIQ scales by Spearman's rank correlation coefficient. Results: For internal reliability, Cronbach's alpha coefficient was calculated as 0.957 for nonworking patients and 0.958 for working patients. Cronbach's alpha values of 0.939, 0.871, and 0.914 were obtained for daily, social, and work life, respectively. Correlation coefficients were 0.888 for daily life, 0.859 for social life, and 0.901 overall in the nonworking group versus 0.896 the in working group. The comparison of scores obtained from test-retest measurements showed no significant difference except for Item 3. The correlation of the symptom severity score (SSS) and the FPQ-T was r=0.385 (p<0.001) and r=0.390 (p<0.001) for the nonworking and working subgroups, respectively. The evaluation of construct validity showed a significant correlation between the SSS and FPQ-T. Conclusion: The results of our study showed that the FPQ-T is reliable and valid for assessing participation and social functioning in fibromyalgia patients in Turkish society.
Keywords: Fibromyalgia; fibromyalgia participation questionnaire; Turkish